The construction, negotiation, and representation of immigrant student identities in South African schools - Vandeyar, Saloshna; Vandeyar, Thirusellvan (Education policy in practice., 2015)
This is a ground-breaking research study on Black immigrant identities in South African schools. It is the first major book on racial integration and immigrant children in South African schools. The overall aim of this study is to investigate how immigrant students negotiate and mediate their identity within the South African schooling context.This study set out to explain this complex phenomenon, guided by the following research objectives: One, to describe how immigrant student identities are framed, challenged, asserted and negotiated within the institutional cultures of schools. Two, to evaluate the extent to which the ethos of these schools has been transformed towards integration in the truest sense and to determine how immigrant students perceive this in practice? Three, to explore the 'transnational social fields' in terms of social networks and cross-border linkages of immigrant students and how this impacts on their identity formation. Four, to determine if there are any new forms of immigrant student self-identities that are beginning to emerge? Five, to determine the extent to which racial desegregation has been accompanied by social integration between immigrant and local students. Six, to determine the impact of the South African social/schooling context on immigrant student identity formation. And seven, to identify critical lessons and 'good practice' that could be learnt and used to accelerate the racial desegregation and social integration of immigrant students in South African schools.